Chest Pain Risk Stratification: A Comparison of the 2-Hour Accelerated Diagnostic Protocol (ADAPT) and the HEART Pathway. Issue 2 (June 2016) - Stopyra, Jason P.; Miller, Chadwick D.; Hiestand, Brian C.; Lefebvre, Cedric W.; Nicks, Bret A.; Cline, David M.; Askew, Kim L.; Riley, Robert F.; Russell, Gregory B.; Burke, Greg L.; Herrington, David; Hoekstra, James W.; et al.
Abstract : Background: The 2-hour accelerated diagnostic protocol (ADAPT) and the history electrocardiogram age risk factors troponin (HEART) Pathway are decision aids designed to identify Emergency Department (ED) patients with chest pain who are safe for early discharge. Both have demonstrated high sensitivity (>99%) for major adverse cardiac events (MACE) at 30 days and early discharge rates ≥20%. The objective of this study is to compare the sensitivity and early discharge rates of the ADAPT and HEART Pathway decision aids in a cohort of ED patients with acute chest pain. Methods: A secondary analysis of participants enrolled and randomized to the HEART Pathway arm of the HEART pathway randomized controlled trial was conducted. Each patient was prospectively classified as low risk (suitable for early discharge) or high risk by ADAPT and the HEART Pathway. Sensitivity for MACE at 30 days and the number of patients identified as low-risk were calculated for each decision aid. Decision aid performance was compared using McNemar's test. Results: MACE occurred in 8 of 141 (5.7%); there were no deaths, 7 patients had myocardial infarction, and 1 patient had coronary revascularization without myocardial infarction. ADAPT and the HEART pathway identified all patients with MACE as high risk; sensitivity for MACE of 100% [95% confidence interval (CI): 63–100%]. ADAPT identified 34 of 141 patients (24%; 95% CI: 17–32%) as low-risk, whereas the Heart pathway identified 66 of 141 patients (47%, 95% CI: 38–55%) as low risk ( P < 0.001). Conclusions: Within a cohort of ED patients with acute chest pain, ADAPT and the HEART pathway had high sensitivity for MACE. The HEART pathway outperformed ADAPT by correctly identifying more patients as low risk and safe for early discharge.